Chinese college students’ mental health during the first three months of the COVID-19 pandemic: the protective role of family functioning - Zeng, Zihao; Holtmaat, Karen; Verdonck-de Leeuw, Irma M.; Koole, Sander L. (Frontiers in Public Health, 2024)
Background Various psychological theories suggest that a supportive family environment protects the mental health of young adults during stressful life events. However, evidence is limited regarding the protective role of family support during a major public health crisis. Objective To examine the role of family functioning on mental health among Chinese college students during first stage of the COVID-19 pandemic. Methods Between January–March 2020, 1,555 college students (44% female, on average 19 years old) from five Chinese universities participated. Participants rated their family functioning on the Family APGAR Index and their mental health on the Psychological Questionnaires for Emergent Events of Public Health, measuring depression, neurasthenia, fear, obsessive-anxiety and hypochondriasis. Results Better family functioning was associated with having fewer psychological symptoms. In addition, we identified three mental health profiles related to the severity across the psychological symptoms: Low-level, medium-level and high-level symptom clusters. Latent profile analysis showed that as family function improved, students were, respectively, 16 to 24% more likely to be in the low-level symptom group, compared to being in the medium symptom group or the high-level symptom group. Conclusion These results support the notion that family support may act as a psychological buffer for young adults during a large-scale public health crisis like the COVID-19 pandemic.